PENGARUH PELATIHAN STRATEGI KOPING TERHADAP MANAJEMEN PERAWATAN DIRI PASIEN DIABETES MELITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS JEMBER KIDUL KABUPATEN JEMBER - Nur Widayati; Wantiyah Wantiyah; Emi Wuri Wuryaningsih (Fakultas Kesehatan Masyarakat, Universitas Jember, 2015)
Self-care management is essential for maintaining blood glucose control so that the complications of diabetes mellitus can be prevented. Coping skills are needed to overcome obstacles in self-care. This study aimed to identify the effect of coping strategy training on self-care management in patients with type 2 diabetes mellitus. The design of study was a non-randomized control group pretest-posttest design. The population was patients with type 2 diabetes in the area of Public Health Center of Jember Kidul. The sampling technique was purposive sampling involving 20 respondents which were divided into 10 respondents as the intervention group and 10 respondents as the control group. The training was conducted once by providing education about diabetes self-care and stress management. Self-care management was measured by using the Summary of Diabetes Self-care Activities (SDSCA) questionnaire. The data were analyzed by Wilcoxon, t dependent, and Mann-Whitney test (α = 0.05). The result revealed a significant increase in the average value of self-care in the intervention group after coping strategy training (p: 0.008) and there was no difference between pretest and posttest in the control group (p: 0.197). Mann-Whitney test showed a significant difference of self-care betweenthe intervention group and control group after the intervention (p = 0.000). It can be concluded that there was a significant effect of coping strategy training on self-care management in patients with type 2 diabetes mellitus. Coping strategy training can be applied to improve self-care management in diabetic patients.Keywords: Diabetes mellitus, self-care management, coping strategy training